ZENHACHI- Modern and safe stingless bee nest for housing area - Faiz, Azizul; Haziman, Zakaria; Diyana, Kamarudin; Nur Kamaliah, Amer (2021)
ZENHACHI is the new trend for stingless bee nest product in Malaysia. The name of the product itself represent the safety of the structure in Japanese which means (safety bee). The design produced modern and simple concept which inspired by the basic structure of Japanese lunch box (Bento). Hexagon shape of the storage represent the beehive itself while full structure indicate the shape of modern flowerpot which is very suitable to be place at housing area. Instead of giving weight at the top shield for safety, it also can be replaced and flowerpot itself as the farmer can put any suitable plant on top of it. The storage will not easily open by the human or other animals to make the bee worker feels safe during foraging process. The farmer also can be less concern on colony surrounding area because of food source provided for the colony to making pollen and honey.